Making sense of credibility in complex information environments: the role of message sidedness, information source, and thinking styles in credibility evaluation online. Issue 7 (6th June 2020) - Flanagin, Andrew J.; Winter, Stephan; Metzger, Miriam J.
ABSTRACT: An experiment using a representative sample of US. Internet users in the context of online encyclopedias is conducted to understand how the type of information source (expert-generated, user-generated, or hybrid [both expert- and user-generated]) and message sidedness (one- versus two-sided) affect perceived information credibility. Additionally, individual differences in cognitive styles, including need for cognition and flexible thinking, are hypothesized to moderate these relationships. Results showed that expert-generated messages are regarded as most credible, whereas two-sided messages were only perceived as more credible than one-sided messages when originating from a hybrid source. Moreover, the effect of message sidedness is stronger among people with higher flexible thinking, but not among those with high need for cognition. This study extends knowledge of source type to include the diversity of possibilities available online today, clarifies how message sidedness and type of information source affect the perceived credibility of online information, and offers new insight into how individual psychological differences affect the evaluation of online information credibility, including the identification of flexible thinking as an important variable in this domain. Results of this study help to clarify how people navigate the wide diversity of information options available today in efforts to locate credible information to guide their attitudes and behaviors.